2005
DOI: 10.1039/b417058j
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects of iridium complexes for highly efficient red OLEDs

Abstract: This study reports substituent effects of iridium complexes with 1-phenylisoquinoline ligands. The emission spectra and phosphorescence quantum yields of the complexes differ from that of tris(1-phenylisoquinolinato-C2,N)iridium(iii)(Irpiq) depending on the substituents. The maximum emission peak, quantum yield and lifetime of those complexes ranged from 598-635 nm, 0.17-0.32 and 1.07-2.34 micros, respectively. This indicates the nature of the substituents has a significant influence on the kinetics of the exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
105
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(115 citation statements)
references
References 40 publications
10
105
0
Order By: Relevance
“…Such Ir complexes have been the subject of extensive works [8] and important applications as phosphorescent dopants in OLEDs fabrication proposed. [8,9] On the other hand, to the best of our knowledge, they have never been mentioned in the photopolymerization area. In this paper, we proposed tris(2-phenylpyridine)-iridium (Ir(ppy) 3 ) as a novel rcPI.…”
Section: Introductionmentioning
confidence: 94%
“…Such Ir complexes have been the subject of extensive works [8] and important applications as phosphorescent dopants in OLEDs fabrication proposed. [8,9] On the other hand, to the best of our knowledge, they have never been mentioned in the photopolymerization area. In this paper, we proposed tris(2-phenylpyridine)-iridium (Ir(ppy) 3 ) as a novel rcPI.…”
Section: Introductionmentioning
confidence: 94%
“…Devices were fabricated with the structure of ITO/NPB (60 nm)/Ir(BPPya) 3 -doped CBP (40 nm)/BPhen (20 nm)/LiF (1 nm)/Al (100 nm), in which Ir(BPPya) 3 worked as the phosphorescent dopant emitter, CBP as the host material, and BPhen was used to serve as the electron-transporting layer. [27] Here, ITO is indium tin oxide, NPB is N,N′-bis- (1-naphthyl)-N,N′-diphenyl,1,1′-biphenyl-4,4′-diamine, and BPhen is 4,7-diphenyl-1,10-phenanthroline. It was found that the best performance was achieved by the device with an Ir(BPPya) 3 doping concentration of 7 % (D1).…”
mentioning
confidence: 99%
“…When the phenyl is replaced by a naphthyl ring, the Ir(1-niq) 2 (acac) or Ir(2-niq) 2 (acac) formed have emission peaks at 664 and 633 nm, respectively. Ir(4F5Mpiq) 3 was reported in 2005 [161] by the same research team who developed Ir(piq) 3 . The maximum EQE is as high as 15.5 % at a more reasonable current density of 1.23 mA/cm 2 , and the EQE remains at 7.9 % at a current density of 120 mA/cm 2 with luminance of 10,000 cd/m 2 .…”
Section: Red Phosphorescent Materialsmentioning
confidence: 78%